2020
DOI: 10.1055/s-0040-1715791
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cold Agglutinin Hemolytic Anemia

Abstract: Novel coronavirus disease 2019 (COVID-19) has spread throughout the world and has infected close to 4 million people. It commonly presents with fever, cough, and fatigue. Due to the high inflammatory response, it is suggested that the coagulation cascade is enhanced causing thrombotic events for many patients. We describe a patient with clinical features of cerebrovascular accident, as well as documented blood clots in bilateral upper extremities. Labs revealed the presence of cold agglutinin hemolytic anemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…Positive direct Coomb's test was shown in 13% of 267 anemic COVID-19 patients and 46% of the other 113 COVID-19 patients (114,115). Furthermore, both warm and cold AIHA have been reported in COVID-19 patients and most of them recovered spontaneously (116)(117)(118)(119)(120)(121)(122). In line with these findings, a 39-year-old man was found to have concomitant Evans syndrome and COVID-19 infection (123).…”
Section: Hematological Manifestationssupporting
confidence: 61%
“…Positive direct Coomb's test was shown in 13% of 267 anemic COVID-19 patients and 46% of the other 113 COVID-19 patients (114,115). Furthermore, both warm and cold AIHA have been reported in COVID-19 patients and most of them recovered spontaneously (116)(117)(118)(119)(120)(121)(122). In line with these findings, a 39-year-old man was found to have concomitant Evans syndrome and COVID-19 infection (123).…”
Section: Hematological Manifestationssupporting
confidence: 61%
“…Till date, there are two case reports describing thromboembolism in patients with COVID-19 infection and cold agglutinin disease. Patil et al described a case of CAD with AIHA, and pulmonary embolism as a presentation of COVID-19 infection, while Maslov et al reported a patient with COVID-19 infection and cold agglutinin hemolytic anemia complicated with stroke and venous thrombosis of bilateral upper extremities [10,11] However, our patient did not exhibit any features of thromboembolism. While patients with COVID-19 infection are generally at elevated risk of thromboembolic complications, AIHA/CAD should be considered as a possible contributory factor.…”
Section: Discussionmentioning
confidence: 50%
“…12 Most recently, about 20 cases of AIHAs (both cold and warm forms) secondary to COVID-19 infection have been reported, with only one fatality. 13 As a result, this case shows us that, although rare, acute tubular necrosis can be seen together with AIHA associated with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 59%